The Application of Total Quality Management in The Production of Garbage Cans at UD. Lima Sarana Bersih, Malang City - Philipus Nerispa Supardi; Cakti Indra Gunawan; Setyaningrum, Fitria (International Journal of Management and Business, 2025)
Total Quality Management (TQM) is a management system that promotes quality as a business strategy and is oriented towards customer. This research aimed to analyze the application of Total Quality Management to the production of garbage cans in UD Lima Sarana Bersih, Malang City. This study used a purposive sampling technique. The type of data in this study uses primary and secondary data. The validity check in this study uses the authorization technique. The results of this study show that UD. Lima Sarana Bersih apply the principles of Total Quality Management in every aspect of production, although overall the total implementation of Total Quality Management in UD. Lima Sarana Bersih, Malang City is good, but there are still things that need to be improved. The implications of this research are UD. Lima Sarana Bersih must be more serious in efforts to improve employee human resources through training and empowerment. On the other hand, the UD. Lima Sarana Bersih needs to make continuous system improvements by continuing to evaluate and improve the effectiveness of the measures that have been taken.